Pure inorganic stimuli-responsive sol as well as preparation method and application thereof
By using pure inorganic one-dimensional nanomaterials and anion adjustment methods, the reversible transformation of inorganic sol and gel is achieved, and the problems of poor thermal stability of inorganic hydrogels and high cost of organic hydrogels in the prior art are solved, and the problems of poor thermal stability of inorganic hydrogels and high cost of organic hydrogels are achieved. Efficient stimulus response performance.
Patent Information
- Application Number
- CN202410483528.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2025-02-07
AI Technical Summary
The existing stimulus response gels are mainly organic hydrogels, which have problems such as poor thermal stability, high cost, toxicity of crosslinking agents and complex preparation. In addition, the organic hydrogel is still formed by purely inorganic materials. The disadvantages of glue.
Pure inorganic one-dimensional nanomaterials are used to repel nanomaterials through the positive charge of rare earth metal elements, forming a sol, and the reversible transformation between the sol and gel is achieved through the adjustment of anion pair.
Inorganic sols that can be monodispersed in water without additional surface modification reagents are realized, and the reversible transformation between the sol and gel is achieved through environmental regulation, with high thermal stability, good mechanical properties and stimulation response capabilities.
Smart Images

Figure CN119390028A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials and biomedicine, and in particular to a pure inorganic stimulus-responsive sol and a preparation method and application field thereof. Background Art
[0002] Products that can complete the conversion between a liquid state (sol) and a semi-solid or solid state (gel) under stimulation conditions are called stimulus-responsive sols or stimulus-responsive gels, such as liquid band-aids, injectable organic gels, 3D printing consumables, etc. The stimulus-responsive conversion from sol state to gel state can provide great convenience and expand the scope of application of the product.
[0003] At present, all stimulus-responsive gels are based on organic hydrogels. Hydrogels in the traditional sense often refer specifically to organic hydrogels that form a three-dimensional network of hydrophilic polymers. However, organic hydrogels are often restricted in use due to their swelling and low mechanical properties. Although the mechanical properties of organic hydrogels have been modified by constructing double network structures, the poor thermal stability, high cost, toxicity of crosslinkers, and complexity of preparation of organic hydrogels are still issues that need to be considered.
[0004] Nowadays, inorganic hydrogels with high thermal stability, high strength and high conductivity are being developed. In terms of formation mechanism, inorganic hydrogels can be divided into inorganic hydrogels formed based on direct cross-linking, inorganic hydrogels formed based on modified ligands and inorganic hydrogels formed based on electrostatic forces. Inorganic hydrogels formed based on direct cross-linking are often composed of disordered one-dimensional inorganic materials that cannot be disentangled, have poor flexibility, are not stimulus-responsive, and have a limited scope of application. Inorganic hydrogels formed based on modified ligands are often composed of zero-dimensional inorganic nanoparticles and relatively expensive ligands, and their gel strength is limited. They are also restricted in practical use and are generally not considered in the preparation of organic hydrogels. Inorganic hydrogels formed based on electrostatic forces, such as ligand-modified gold nanoparticles, graphene nanosheets, two-dimensional titanium oxide nanosheets and other materials, have good gel properties, and some scholars have studied their temperature responsiveness. However, due to factors such as high prices and complicated preparation steps, these materials are not currently widely used.
[0005] If inorganic materials are simply added to the organic hydrogel matrix to form an organic-inorganic composite gel, although the preparation cost is saved and stimulus-responsive gel properties are obtained, it still has the disadvantages of organic hydrogels because it is mainly composed of organic materials. Summary of the invention
[0006] The first purpose of the present invention is to provide a pure inorganic stimuli-responsive sol in view of the shortcomings of existing stimuli-responsive gels. This pure inorganic stimuli-responsive sol not only maintains the advantages of inorganic gels in thermal stability, ionic conductivity, strength, and resistance to light damage, but also has the stimuli-responsive performance of organic gels. Through the selection of components and the adjustment of the solution environment, the positive charge on the surface of one-dimensional inorganic nanomaterials can resist the aggregation of particles, and can be monodispersed in water to form a sol without the need to add additional surface modification reagents. By adjusting the interaction between nanomaterials through temperature or anions, their dispersion and aggregation conditions can be converted to selectively form sols and gels. This ability to disperse nanomaterials through anions is occasionally used in sols and preparation of precipitation samples. However, the reversible adjustment of one-dimensional sols and gels, and the use of this performance for application, is the first case in the application of pure inorganic materials.
[0007] A pure inorganic stimulus-responsive sol, wherein the stimulus response at least includes a transition response from a sol to a gel. The pure inorganic stimulus-responsive sol includes an inorganic one-dimensional nanomaterial and a solution for dispersing the inorganic one-dimensional nanomaterial; the inorganic one-dimensional nanomaterial contains at least a rare earth metal element, and due to the positive charge of the rare earth metal element, the inorganic one-dimensional nanomaterials repel each other to form a sol.
[0008] Preferably, the inorganic one-dimensional nanomaterial is at least one of phosphates of rare earth metal elements, borates of rare earth metal elements, oxides of rare earth metal elements or hydroxides of rare earth metal elements.
[0009] Preferably, the concentration of the inorganic one-dimensional nanomaterial in the pure inorganic stimuli-responsive sol is 1-100 mg / mL.
[0010] Preferably, the solution includes anion I, and anion I includes at least one of chloride ion, nitrate ion, borate ion, citrate ion and acetate ion.
[0011] Preferably, the concentration of anion I in the solution is 0.001-10M.
[0012] Preferably, the solution further comprises hydroxide ions, and the concentration of the hydroxide ions is below 1 mM.
[0013] Preferably, the condition of the stimulus response is at least one of the concentration or temperature of anions that can have a chelating effect or electrostatic effect with the metal elements in the inorganic one-dimensional nanomaterial; more preferably, the anions that can have a strong interaction with the metal elements in the inorganic one-dimensional nanomaterial are anions with a high polarizability.
[0014] The stimulus response method of the above pure inorganic stimulus response sol is: adding anions to the sol to form a gel.
[0015] The anions include, but are not limited to, hydroxide ions and anions that can chelate metals. For example, hydroxide ions are added to the aqueous sol of the one-dimensional inorganic nanophosphate material, lysine is added to the aqueous sol of the one-dimensional inorganic nanophosphate material (to change the pH and increase the hydroxide concentration), and EDTA anions are added to the aqueous sol of the one-dimensional inorganic nanoborate material.
[0016] The above-mentioned reversible transformation method of pure inorganic stimulus-responsive sol includes: adding an acidic solution (such as hydrochloric acid) to the gel, adjusting its pH to below 3, and mixing to achieve the transformation from gel to sol; and removing anions in the solution by dialysis or ultrafiltration in an acid solution to achieve the transformation from gel to sol.
[0017] The second object of the present invention is to provide a method for preparing a pure inorganic stimuli-responsive sol, comprising the following steps: step (1), adding an inducer to a metal salt solution under stirring conditions to form a uniform liquid; Step (2), adding liquid into a reaction kettle for reaction; Step (3), controlling the environmental hydroxide concentration to obtain a sol product.
[0018] Preferably, the metal salt in step (1) comprises a salt of a rare earth metal element.
[0019] Preferably, the rare earth metal element is at least one of lanthanum, cerium, spectrium, promethium, samarium, europium and gadolinium.
[0020] Preferably, the anions in the metal salt in step (1) include at least one of nitrate ions, acetate ions, sulfate ions, chloride ions, bromide ions, and iodide ions.
[0021] Preferably, the concentration of the metal salt in step (1) is 0.1-10M.
[0022] Preferably, the inducing agent in step (1) comprises an alkaline solution.
[0023] Preferably, the alkaline solution includes at least one of aqueous ammonia, sodium hydroxide and potassium hydroxide.
[0024] Preferably, the inducing agent in step (1) further comprises an oxygen-containing acid.
[0025] Preferably, the oxygen-containing acid comprises at least one of concentrated phosphoric acid or boric acid.
[0026] Preferably, the reaction time of step (2) is less than 24 hours, and the reaction temperature is 60-300°C.
[0027] Preferably, in step (3), the hydroxide concentration is controlled to be less than 1 mM.
[0028] Preferably, the method for controlling the hydroxide concentration in step (3) is to use an acid.
[0029] Preferably, the acid comprises at least one of hydrochloric acid, nitric acid, boric acid, citric acid or acetic acid.
[0030] Preferably, the oxygen-containing acid solution is a metal oxygen-containing acid solution or a non-metal oxygen-containing acid solution, and the pH of the oxygen-containing acid solution is less than 5; Preferably, the pH of the alkaline solution is greater than 9; The third object of the present invention is to provide a method for converting a pure inorganic stimuli-responsive sol into a gel in a stimuli-responsive manner.
[0031] The stimulus response conditions include adding anions II that can have chelation and / or electrostatic effects with metal elements in inorganic one-dimensional nanomaterials into the pure inorganic stimulus response sol or changing the temperature of the pure inorganic stimulus response sol.
[0032] Preferably, the anion II that can have a chelating effect and / or electrostatic effect with the metal element in the inorganic one-dimensional nanomaterial includes at least one of hydroxide ion, phosphate ion, carbonate ion, molybdate ion, tungstate ion, titanate ion, sulfate ion, and bismuth ion.
[0033] Preferably, the anion II is a hydroxide ion.
[0034] Preferably, the anion II is a hydroxide ion, and the anion is added to an anion concentration of 0.001M or more.
[0035] Preferably, changing the temperature of the pure inorganic stimuli-responsive sol is to increase the temperature of the sol.
[0036] Preferably, when the added concentration of anions is 0.001 M, the gel transition temperature is 37 degrees Celsius.
[0037] A fourth object of the present invention is to provide a purely inorganic stimuli-responsive gel.
[0038] The fifth object of the present invention is to provide a method for converting a pure inorganic stimuli-responsive gel into a pure inorganic stimuli-responsive sol.
[0039] The stimulus response conditions include removing the anion II or changing the gel temperature.
[0040] Preferably, the specific method for removing the anion II includes adding an acidic solution, dialysis or ultrafiltration.
[0041] Preferably, the acidic solution includes at least one of hydrochloric acid, nitric acid, boric acid, citric acid and acetic acid.
[0042] Preferably, the concentration of the acidic solution is 1M; Preferably, the acidic solution is added to a hydroxide concentration of 0.001 M or less.
[0043] Preferably, the dialysis time is greater than 12 hours, and the ultrafiltration time is greater than 10 minutes; the external solution used in the dialysis is one or more of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.
[0044] Preferably, changing the gelling temperature is lowering the gelling temperature.
[0045] Preferably, when the concentration of anions added is 0.001 M, the gel temperature is reduced to below 37 degrees Celsius.
[0046] The sixth object of the present invention is to provide a pure inorganic stimuli-responsive sol for use in sterilization, hemostasis, wound recovery, drug carrier, medical excipient, cosmetic material or sunscreen product, characterized in that it at least comprises a step of converting the sol into a gel and / or a step of converting the gel into a sol; The pure inorganic stimulus-responsive sol includes an inorganic one-dimensional nanomaterial and a solution for dispersing the inorganic one-dimensional nanomaterial; the inorganic one-dimensional nanomaterial contains at least a rare earth metal element, and due to the positive charge of the rare earth metal element, the inorganic one-dimensional nanomaterials repel each other to form a sol.
[0047] The seventh object of the present invention is to provide a pure inorganic stimuli-responsive gel for use in sterilization, hemostasis, wound recovery, drug carrier, medical adjuvant, cosmetic material or sunscreen product, characterized in that it at least comprises a step of converting a gel into a sol and / or a step of converting a sol into a gel; The sol includes an inorganic one-dimensional nanomaterial and a solution for dispersing the inorganic one-dimensional nanomaterial; the inorganic one-dimensional nanomaterial contains at least a rare earth metal element, and due to the positive charge of the rare earth metal element, the inorganic one-dimensional nanomaterials repel each other to form a sol.
[0048] The applications include, but are not limited to, applications in bactericides, disinfectants, antibacterial agents, liquid wound dressings, hemostatic gels, hemostatic films, wet gauze, hemostatic patches, gel excipients, liquid excipients, gel dressings, liquid dressings, foam dressings, facial masks, facial creams, essences, body lotions, sunscreen lotions, sunscreen milks, and sunscreen creams.
[0049] Therefore, the present invention has the following beneficial effects: The present invention solves the technical problem of the transformation of one-dimensional inorganic nanomaterial sol to gel by inorganic nanomaterials with positive charge. First, compared with inorganic nanoparticles of other morphologies, one-dimensional inorganic nanomaterials have a good stimulus-responsive sol-gel transformation basis. Secondly, the metal ions on the surface of one-dimensional inorganic nanomaterials carry positive charges sufficient to resist particle aggregation, and can be monodispersed in water to form a sol without the need to add additional surface modification reagents. One-dimensional inorganic nanomaterials can be cross-linked when anions are added, and stimulated to form gels. Compared with the means of providing positive charges for one-dimensional inorganic nanomaterials by modification means, this kind of one-dimensional inorganic nanomaterials carrying positive charges themselves, in addition to only requiring cheap inorganic substances in terms of cost, have qualitative changes in convenience and cost in further processing and practical applications, and do not need to replace ligands to achieve the regulation of the forces between one-dimensional inorganic nanomaterials, and have extremely high advantages in achieving stimulus-responsive sol-gel transformation capabilities.
[0050] The present invention uses hard, difficult-to-stimulate inorganic materials to prepare stimulus-responsive gels, expands the application field of inorganic materials, and successfully realizes that one-dimensional inorganic nanomaterials form hydrogels through inter-ionic forces and can return to a sol state. Inorganic nanomaterials with strong positive charges on the surface and the three-dimensional network structures formed by them can also have stimulus-responsive capabilities, because the forces between their one-dimensional materials can be adjusted by the environment, and reversible transformations between sol and gel can be achieved.
[0051] The method of the present invention is low in cost and easy to operate. The prepared hydrogel has both good mechanical properties and good stimulus response capabilities, and is a material that can be used in a comprehensive manner. By adjusting its size factor, its gel transition properties can be changed to make it suitable for a variety of practical needs, such as liquid dressings for wounds, facial gel dressings for beauty, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 These are transmission electron micrographs of the lanthanum phosphate, cerium phosphate, and praseodymium phosphate nanowires in Example 1 under acidic and alkaline conditions.
[0053] Figure 2 This is a photograph of the transition between sol and gel of the lanthanum phosphate nanowire sol in Test Example 1 by sodium hydroxide and hydrochloric acid.
[0054] Figure 3 In order to test the mechanical properties of the lanthanum phosphate nanowire sol in Example 1 in both the sol and gel states through sodium hydroxide and hydrochloric acid, a total of 4 cycles were performed.
[0055] Figure 4 This is a photograph of the transition of the lanthanum phosphate nanowire sol between sol and gel through temperature change in Test Example 1.
[0056] Figure 5AThis is an electron microscope image of the iron-doped cerium phosphate nanowire sol in Example 2.
[0057] Figure 5B This is the energy spectrum of the iron-doped cerium phosphate nanowire sol in Example 2.
[0058] Figure 5C This is the element distribution diagram of the iron-doped cerium phosphate nanowire sol in Example 2.
[0059] Figure 6 This is a photograph of the transition between sol and gel of the iron-doped cerium phosphate nanowire sol in Test Example 2 by sodium hydroxide and hydrochloric acid.
[0060] Figure 7 In order to test the mechanical properties of the iron-doped cerium phosphate nanowire sol in Example 2 in both the sol and gel states through sodium hydroxide and hydrochloric acid, a total of 4 cycles were performed.
[0061] Fig. 8A Element distribution diagram of copper-doped cerium phosphate nanowire sol in Test Example 2.
[0062] Figure 8B Element distribution diagram of manganese-doped cerium phosphate nanowire sol in Test Example 2.
[0063] Fig. 9 This is a transmission electron micrograph of the transformation of lanthanum borate, praseodymium borate, and samarium borate nanorods between sol and gel by sodium hydroxide and hydrochloric acid in Example 4.
[0064] Fig.10 This is a photograph of the transition between sol and gel of lanthanum borate nanorods in Test Example 4 by sodium hydroxide and hydrochloric acid.
[0065] Fig.11 This is a transmission electron micrograph of the transformation of lanthanum hydroxide and praseodymium hydroxide nanorods between sol and gel by sodium hydroxide and hydrochloric acid in Example 5.
[0066] Fig.12 This is a photograph of the transition between sol and gel of lanthanum hydroxide nanorods in Test Example 5 by sodium hydroxide and hydrochloric acid.
[0067] Fig.13 This is a transmission electron microscope image of cerium oxide, titanium oxide, aluminum oxide and vanadium oxide nanowires in Example 6, in which from left to right are: cerium oxide, titanium oxide, aluminum oxide, vanadium oxide.
[0068] Fig.14 These are photos and transmission electron microscope images of the transition of cerium oxide nanowires between sol and gel by sodium hydroxide and hydrochloric acid in Test Example 6.
[0069] Fig.15This is a photograph of the transition between sol and gel of the cerium phosphate nanowire sol in Example 7 through bacterial growth solution and hydrochloric acid.
[0070] Fig.16 This is a diagram of the colony status after co-culturing cerium phosphate nanowires doped with different degrees of iron and Escherichia coli in Example 7.
[0071] Fig.17 The colony status diagram and statistical diagram of the co-culture of cerium phosphate nanowires doped with different degrees of iron and Staphylococcus aureus in Example 7.
[0072] Fig.18 The colony status diagram and statistical diagram of the co-culture of cerium phosphate nanowires doped with different degrees of iron and Pseudomonas aeruginosa in Example 7.
[0073] Fig.19 This is a scanning electron microscope image of the cerium phosphate nanowires doped with different degrees of iron after co-culture with Escherichia coli in Example 7.
[0074] Fig. 20 This is a graph of bleeding time after using cerium phosphate and sodium chloride solution in the mouse venous hemostasis experiment in Example 8.
[0075] Fig.21 This is a graph of bleeding time after using cerium phosphate and sodium chloride solutions in the Dutch rabbit vein, artery hemostasis experiment and liver hemostasis experiment in Example 8.
[0076] Fig. 22 This is a comparison chart of the bleeding time of cerium phosphate liquid and powder in the Dutch rabbit artery hemostasis experiment in Comparative Example 1.
[0077] Fig.23 This is a comparison chart of the bleeding time using cerium phosphate liquid and chitosan gel in the Dutch rabbit artery hemostasis experiment in Comparative Example 2.
[0078] Fig.24 This is a transmission electron micrograph of the transition of the cerium phosphate nanowire sol between sol and gel in Example 9 through body fluid and hydrochloric acid.
[0079] Fig.25 This is a graph showing the antioxidant activity of cerium phosphate nanowires doped with different degrees of iron in Example 9.
[0080] Fig.26 This is a graph showing the recovery of the mouse full wound defect model in Example 9 under different degrees of iron-doped cerium phosphate nanowires.
[0081] Fig. 27 This is the SOD activity diagram of cerium phosphate nanowires doped with different degrees of iron in Example 10.
[0082] Fig.28This is a transmission electron micrograph of the transition between sol and gel of lanthanum phosphate nanowires loaded with vitamin C in Example 11 by sodium hydroxide and hydrochloric acid.
[0083] Fig.29 This is a photograph of the transition between sol and gel of lanthanum phosphate nanowires loaded with vitamin C in Example 11 by sodium hydroxide and hydrochloric acid.
[0084] Fig.30 This is the ultraviolet-visible light absorption diagram of the lanthanum phosphate nanowires in Example 12.
[0085] Fig.31 This is the ultraviolet-visible light absorption diagram of the praseodymium phosphate nanowires in Example 12.
[0086] Fig.32 This is the ultraviolet-visible light absorption diagram of the lanthanum borate nanorods in Example 12.
[0087] Fig.33 This is a transmission electron microscope image of the samarium hydroxide, gadolinium hydroxide and dysprosium hydroxide nanorods in Comparative Example 3. DETAILED DESCRIPTION
[0088] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0089] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0090] Example 1 Weigh 7.4 g of lanthanum nitrate (molecular weight 324.92, 0.023 mol) and add it to 20 mL of deionized water, stirring magnetically until dissolved. Take 0.6 mL of commercial concentrated phosphoric acid (85%) and add it to 20 mL of deionized water, and take 0.4 mL of ammonia water (28%) to mix. Slowly add the latter to the former under vigorous stirring. After the addition is completed, ultrasonicate for 30 min and stir vigorously again for 6 h. When the transparency of the solution increases and the solution becomes thicker, add the liquid to the reactor and react at 250 ° C for 24 h. After the reaction is completed, centrifuge the reactants and redisperse them in water, repeat 5 times. Finally, the product is dispersed in 10 mL of hydrochloric acid solution with pH = 2 to obtain lanthanum phosphate nanowire sol.
[0091] By replacing lanthanum nitrate with an equal molar amount of cerium nitrate, praseodymium nitrate, promethium nitrate, samarium nitrate, europium nitrate, gadolinium nitrate and other raw materials, the corresponding metal phosphate nanowires can be prepared, which also have the above-mentioned properties.
[0092] Figure 1 TEM images of lanthanum phosphate, cerium phosphate and praseodymium phosphate nanowires in Example 1 under acidic and alkaline conditions; Figure 1 It can be seen that the prepared material is a one-dimensional nanofiber with a diameter of about 10 nm and a length of about 1000 nm.
[0093] Test Example 1 Hydroxyl ions were added to the lanthanum phosphate nanowire sol prepared in Example 1. The dispersibility of the material could be changed by changing the pH value (hydroxyl concentration) of the solution sample. The specific condition was to add 50 μL of NaOH at pH 14 to 5 mL of 30 mg / mL sol.
[0094] Depend on Figure 2 It can be seen that after adding 50 μL of NaOH at pH 14 to 5 mL of 30 mg / mL lanthanum phosphate sol, a lanthanum phosphate gel can be formed. By adding 50 μL of hydrochloric acid solution at pH 0 again, it can be turned back into a sol. In an alkaline environment, the hydroxide concentration is high, and the hydroxide can act as a "binder" between nanowires, cross-linking the nanowires to form a gel. In an acidic environment (by adding sodium hydroxide), the hydroxide decreases sharply, the nanowires lose the "binder", and redisperse to form a sol.
[0095] 1 mL of 30 mg / mL lanthanum phosphate sol was taken to test its rheological properties. After adding 10 μL of pH 14 NaOH solution, its rheological properties were tested again. Then, 10 μL of pH 0 HCl solution was added to test its rheological properties again, and this was repeated 4 times.
[0096] Depend on Figure 3 It can be seen that G' is the storage modulus, G'' is the loss modulus, 1G'-8G' and 1G''-8G'' are the changes in the modulus during the four sol and gel cycles, respectively. It can be seen that the material has good reversible performance transformation performance.
[0097] The lanthanum phosphate nanowire sol prepared in Example 1 is heated; Figure 4 It can be seen that by changing the temperature, it can also be transformed between sol and gel.
[0098] The transition from sol to gel can also be achieved by adding other anions, but since they are difficult to remove, it is not easy to return from gel to sol. The specific addition amounts are shown in Table 1.
[0099] Table 1 Minimum concentrations of different reagents required for the conversion of lanthanum phosphate nanowire sol from sol to gel substance Chemical formula Gel concentration (mM) Potassium ferrocyanide <![CDATA[K 4 Fe(CN) 6 ]]> 0.0233 Sodium molybdate <![CDATA[Na 2 MoO 4 ]]> 0.0367 Sodium Tungstate <![CDATA[Na 2 WHERE 4 ]]> 0.0567 oxalic acid <![CDATA[H 2 C 2 O 4 ]]> 0.183 sulfuric acid <![CDATA[H 2 SO 4 ]]> 0.667 Disodium EDTA EDTA-2Na 2 Phosphoric acid <![CDATA[H 3 AFTER 4 ]]> 5.667 Sodium dihydrogen phosphate <![CDATA[NaH 2 AFTER 4 ]]> 5.667 Disodium hydrogen phosphate <![CDATA[Na 2 HPO 4 ]]> 5.667 Sodium Hydrosulfide NaHS 8 Ammonium bicarbonate <![CDATA[NH 4 HCO 3 ]]> 8.333 Fluorosilicic acid <![CDATA[H 2 SiF 6 ]]> 11.667 Ammonium fluoride <![CDATA[NH 4 F]]> 15 tartaric acid <![CDATA[HOOC(CHOH) 2 COOH]]> 26.667 Table 2 Substances with high concentrations required for the conversion of lanthanum phosphate nanowire sol from sol to gel substance Chemical formula Gel concentration (mM) Nitric acid <![CDATA[HNO 3 ]]> >1000 Boric acid <![CDATA[H 3 BO 3 ]]> >1000 acetic acid <![CDATA[CH 3 COOH]]> >1000 Ammonium bromide <![CDATA[NH 4 Br]]> >1000 Citric Acid <![CDATA[HOCCOOH(CH 2 COOH) 2 ]]> >1000 Potassium thiocyanate KSCN >1000 Ethanol <![CDATA[CH 3 CH 2 OH]]> No gel in pure ethanol It can be seen that it is difficult to transform the sol into gel for the substances in Table 2.
[0100] Example 2 Weigh 7.4 g of cerium nitrate and 1.3 g of ferric nitrate and add them to 20 mL of deionized water, and stir them magnetically until dissolved. Take 0.6 mL of commercial concentrated phosphoric acid (85%) and add it to 20 mL of deionized water, and take 0.3 mL of ammonia water (25%-28%) and mix them. Slowly add the latter to the former under vigorous stirring. After the addition is completed, ultrasonicate for 30 min and stir vigorously again for 6 h. When the transparency of the solution increases and the solution becomes thicker, add the liquid to the reactor and react at 250 ℃ for 24 h. After the reaction is completed, centrifuge the reactants and redisperse them in water, repeat 5 times. Finally, the product is dispersed in 10 mL of hydrochloric acid solution with pH=2 to obtain iron-doped cerium phosphate nanowire sol.
[0101] As can be seen from FIG5 , the prepared material is a one-dimensional nanowire; the energy spectrum and element distribution diagram can determine that the iron element is successfully incorporated into the nanowire.
[0102] Test Example 2 Hydroxyl ions were added to the sol prepared in Example 2. Figure 6 It can be seen that by adding hydrochloric acid and sodium hydroxide to adjust the pH environment of the solution, the material can be reversibly transformed between the sol and gel states.
[0103] Take 1mL of 30mg / mL sol and test its rheological properties. Then add 10μL of pH 14 NaOH solution and test its rheological properties again. Then add 10μL of pH 0 NaOH solution and test its rheological properties again. Repeat 4 times. Figure 7 It can be seen that G' is the storage modulus, G'' is the loss modulus, 1G'-8G' and 1G''-8G'' are the changes in the modulus during the 4 cycles, respectively. It can be seen that the material has good reversible transformation performance.
[0104] By replacing cerium nitrate with an equal molar amount of other raw materials such as lanthanum nitrate, praseodymium nitrate, promethium nitrate, samarium nitrate, europium nitrate, and gadolinium nitrate, the corresponding iron-doped metal phosphate nanowires can be prepared, which also have the above-mentioned properties.
[0105] By replacing iron nitrate with other raw materials such as cobalt nitrate, copper nitrate, nickel nitrate, manganese nitrate, etc., other metal-doped cerium phosphate nanowires can be prepared with the same properties as above. The element distribution diagrams of copper-doped cerium phosphate and manganese-doped cerium phosphate are shown in Figure 8.
[0106] Similar to Example 1, the transformation from sol to gel can also be achieved by changing the temperature and adding other anions.
[0107] Example 3 Weigh 7.4 g of lanthanum nitrate and add it to 20 mL of deionized water. Stir magnetically until dissolved. Take 0.84 g of boric acid (99.99%) and dissolve it in 20 mL of deionized water, and mix it with 0.8 mL of ammonia water (25%-28%). Slowly add the latter to the former under vigorous stirring. After the addition is complete, ultrasonicate for 5 minutes and stir vigorously again for 1 hour. When the transparency of the solution increases and the solution becomes thicker, add the liquid to the reactor and react at 250 ° C for 24 hours. After the reaction is completed, centrifuge the reactants and redisperse them in water. Repeat 5 times. Finally, the product is dispersed in 10 mL of deionized water to obtain lanthanum borate nanorods.
[0108] Test Example 3 Hydroxyl ions were added to the sol prepared in Example 4. Fig. 9 It can be seen that the prepared material is a one-dimensional nanorod with a diameter of about 10 nm and a length of about 400 nm; the dispersibility of the material can be changed by changing the pH value (hydroxyl concentration) of the solution sample.
[0109] Depend on Fig.10 It can be seen that when 50 μL of pH 14 NaOH is added to 5 mL of 30 mg / mL sol, a gel is formed. By adding 50 μL of pH 0 hydrochloric acid solution again, it can be turned back into a sol.
[0110] Similar to Example 1, the transformation from sol to gel can also be achieved by changing the temperature and adding other anions.
[0111] By replacing lanthanum nitrate with an equal molar amount of other raw materials such as cerium nitrate, praseodymium nitrate, promethium nitrate, samarium nitrate, europium nitrate, and gadolinium nitrate, the corresponding metal borate nanorods can be prepared, which also have the above-mentioned properties.
[0112] Example 4 Weigh 8.68 g of lanthanum nitrate (99.99%) and add it to 20 mL of deionized water. Stir magnetically until dissolved. Take 14.4 g of sodium hydroxide (99.99%) and dissolve it in 20 mL of deionized water. Slowly add the latter to the former under vigorous stirring. After the addition is complete, ultrasonicate for 5 min and stir vigorously again for 1 h. Add the liquid to the reactor and react at 80 ° C for 24 h. After the reaction is completed, centrifuge the reactants and redisperse them in water. Repeat 8 times. Finally, the product is dispersed in 10 mL of pH 4 hydrochloric acid solution to obtain lanthanum hydroxide nanowires.
[0113] Test Example 4 Hydroxyl ions were added to the sol prepared in Example 5. Fig.11 It can be seen that the prepared material is a one-dimensional nanowire with a diameter of about 15 nm and a length of about 600 nm; the dispersibility of the material can be changed by changing the pH value (hydroxyl concentration) of the solution sample.
[0114] Depend on Fig.12 It can be seen that when 50 μL of pH 14 NaOH is added to 5 mL of 30 mg / mL sol, a gel is formed. By adding 50 μL of pH 0 hydrochloric acid solution again, it can be turned back into a sol.
[0115] Similar to Example 1, the transformation from sol to gel can also be achieved by changing the temperature and adding other anions.
[0116] By replacing lanthanum nitrate with an equal molar amount of other raw materials such as praseodymium nitrate, promethium nitrate, samarium nitrate, europium nitrate, and gadolinium nitrate, the corresponding metal hydroxide nanowires can be prepared, which also have the above-mentioned properties.
[0117] Example 5 Weigh 8.68 g of cerium nitrate (99.99%) and add it to 20 mL of deionized water. Stir magnetically until dissolved. Take 14.4 g of sodium hydroxide (99.99%) and dissolve it in 20 mL of deionized water. Slowly add the latter to the former under vigorous stirring. After the addition is complete, ultrasonicate for 5 min and stir vigorously again for 1 h. Add the liquid to the reactor and react at 80 ° C for 24 h. After the reaction is completed, centrifuge the reactants and redisperse them in water. Repeat 8 times. Finally, the product is dispersed in 10 mL of hydrochloric acid solution with pH = 4 to obtain a cerium oxide one-dimensional material.
[0118] By replacing cerium nitrate with aluminum nitrate, vanadium nitrate, and titanium oxide, the corresponding oxide one-dimensional nanomaterials can be prepared. Fig.13 shown.
[0119] Test Example 5 Hydroxyl ions were added to the sol prepared in Example 6. Fig.14 It can be seen that a gel can be formed by adding 50 μL of NaOH at pH 14 to 5 mL of 30 mg / mL cerium oxide one-dimensional material sol. By adding 50 μL of hydrochloric acid solution at pH=0 again, it can be turned back into a sol.
[0120] Similar to Example 1, the transformation from sol to gel can also be achieved by changing the temperature and adding other anions.
[0121] Example 6 Cerium phosphate nanowires with different iron doping ratios were prepared using the preparation method in Example 2 for investigation of bactericidal properties.
[0122] Depend on Fig.15 It can be seen that by contacting the bacterial growth environment and adding hydrochloric acid, the material can be reversibly transformed between the sol and gel states. Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa were cultured in the presence of iron-doped cerium phosphate, and their bactericidal properties were tested by counting colonies on plates.
[0123] Depend on Fig.16 , 17 , 18, it can be seen that the nanowire itself has bactericidal properties, and the iron doping further improves its bactericidal ability. Fig.23 It can be seen that the material can contact bacteria and kill them.
[0124] Example 7 The cerium phosphate nanowires in Example 1 were used to investigate the hemostatic properties.
[0125] In order to explore the hemostatic performance of the material, a mouse tail-cut model was established, and the hemostatic time of the mice was recorded to evaluate the hemostatic ability of the material.
[0126] Depend on Fig. 20 It can be seen that in the environment of sol-gel reversible transformation materials, the hemostasis time of mice was greatly shortened.
[0127] For further study, arterial bleeding model and liver bleeding model of Dutch rabbit were established, and the hemostatic ability of the material was evaluated by recording the hemostasis time.
[0128] Depend on Fig.21 It can be seen that under the action of this material, the bleeding time of both models is greatly shortened.
[0129] Comparative Example 1 Cerium phosphate nanowire solid powder was used to study the arterial hemostatic properties.
[0130] Depend on Fig. 22It can be seen that compared with the results in Example 7, the hemostatic effect of the solid powder with the same solid content is not good. The reason is that the dry powder has agglomerated and cannot be dispersed in the blood and cross-linked. It cannot fully contact and coagulate with the blood, and it is difficult to produce a sol effect.
[0131] Comparative Example 2 Compared with common organic gels, chitosan hydrogel was synthesized in acetic acid solution using chitosan as raw material and glutaraldehyde as crosslinking agent. The chitosan concentration was 2.5% and the glutaraldehyde concentration was 1%. The chitosan hydrogel was prepared at a temperature of 45 degrees Celsius and used for hemostasis test. Fig.23 It can be seen that the hemostatic time is slightly longer than that in Example 7. It can be seen that due to the sol-gel transition effect, the hemostatic effect of the cerium phosphate sol is slightly higher than that of the ordinary gel.
[0132] In terms of the price of the main raw materials, chitosan costs 100-200 yuan / kg, while cerium nitrate costs only around 20 yuan / kg, which has a great cost advantage.
[0133] Example 8 The iron-doped cerium phosphate nanowires in Example 2 were used to investigate wound recovery.
[0134] Depend on Fig.24 It can be seen that by contacting the body fluid environment and adding hydrochloric acid, the material can be reversibly transformed between the sol and gel states.
[0135] In order to explore the effect of materials on wound recovery, the ability of materials to remove reactive oxygen species was tested by using PTIO. Fig.25 It can be seen that cerium phosphate itself has a certain ability to remove active oxygen, and the incorporation of iron can greatly improve this performance, thereby promoting wound recovery.
[0136] In order to explore the promoting effect of the material on wound recovery, a mouse upper full-thickness cortical excision wound model was established. The iron-doped cerium phosphate sol-gel reversible transformation inorganic nanomaterial formed a coating layer with body fluids at the wound site. The wound recovery was observed and its ability to promote wound recovery was evaluated.
[0137] Fig.26 It can be seen that the iron-doped cerium phosphate sol-gel reversibly transforms into inorganic nanomaterials and promotes wound recovery.
[0138] Example 9 The iron-doped cerium phosphate nanowires in Example 2 were used to explore the cosmetic effect.
[0139] Depend on Fig. 27As shown, by testing the SOD enzyme performance of the material with pyrogallol, it can be found that the material with a specific doping degree has the best biocatalytic performance. This shows that in addition to the antioxidant activity in Example 9, the material also has a certain SOD activity and can be used as a cosmetic material.
[0140] Example 10 Weigh 7.4 g of lanthanum nitrate and add it to 20 mL of deionized water. Stir magnetically until dissolved. Take 0.6 mL of commercial concentrated phosphoric acid and add it to 20 mL of deionized water, and mix it with 0.4 mL of ammonia water. Slowly add the latter to the former under vigorous stirring. After the addition is completed, ultrasonicate for 30 min and stir vigorously again for 6 hours. When the transparency of the solution increases and the solution becomes thicker, add the liquid to the reactor and react at 250 ° C for 24 hours. After the reaction is completed, centrifuge the reactants and redisperse them in water, repeat 5 times. Finally, the product is dispersed in 10 mL of hydrochloric acid solution with a pH of 2 to obtain a lanthanum phosphate nanowire sol. Add 0.1 g of vitamin C to the liquid and disperse it by ultrasound.
[0141] Depend on Fig.28 It can be seen that the prepared material is a one-dimensional nanofiber; the dispersibility of the material can be changed by changing the hydroxide concentration of the solution sample, and vitamin C has no interference with its sol-gel reversible properties.
[0142] Depend on Fig.29 It can be seen that after adding 50 μL of NaOH at pH=14 to 5 mL of 30 mg / mL sol, a gel can be formed. By adding 50 μL of hydrochloric acid solution at pH=0 again, it can be turned back into a sol. Vitamin C does not interfere with its sol-gel reversibility.
[0143] Embodiment 11 The UV-visible light absorption test is used to detect the UV absorption ability of the material.
[0144] Depend on Fig.30 It can be seen that the lanthanum phosphate in Example 1 has a high absorption capacity in both UVA and UVB ultraviolet bands and can be used as an ultraviolet absorber.
[0145] Depend on Fig.31 It can be seen that the praseodymium phosphate in Example 1 has similar ultraviolet absorption ability.
[0146] Depend on Fig.32 It can be seen that the lanthanum borate in Example 4 also has similar ultraviolet absorption ability.
[0147] Comparative Example 3 Weigh 7.4 g of samarium nitrate and add it to 20 mL of deionized water. Stir magnetically until dissolved. Take 0.6 mL of commercial concentrated phosphoric acid and add it to 20 mL of deionized water, and mix it with 0.4 mL of ammonia water. Slowly add the latter to the former under vigorous stirring. After the addition is completed, ultrasonicate for 30 min and stir vigorously again for 6 hours. When the transparency of the solution increases and the solution becomes thicker, add the liquid to the reactor and react at 250 ° C for 24 hours. After the reaction is completed, centrifuge the reactants and redisperse them in water, repeat 5 times. Finally, the product is dispersed in 10 mL of hydrochloric acid solution with pH 2 to obtain a one-dimensional sol of samarium hydroxide. Gadolinium hydroxide and dysprosium hydroxide can be obtained by replacing nitric acid with gadolinium nitrate and dysprosium hydroxide.
[0148] Depend on Fig.33 It can be seen that the prepared samarium hydroxide, gadolinium hydroxide and dysprosium hydroxide are all nanorods with a size greater than 50 nm, and have no gel transition characteristics.
Claims
1. A pure inorganic stimulus-responsive sol, wherein the stimulus response at least includes a transition response from sol to gel; characterized in that: The pure inorganic stimuli-responsive sol includes an inorganic one-dimensional nanomaterial and a solution for dispersing the inorganic one-dimensional nanomaterial; the inorganic one-dimensional nanomaterial contains at least a rare earth metal element, and the positive charge of the rare earth metal element causes the inorganic one-dimensional nanomaterials to repel each other to form a sol.
2. The pure inorganic stimuli-responsive sol according to claim 1, characterized in that: The inorganic one-dimensional nanomaterial includes at least one of phosphates of rare earth metal elements, borates of rare earth metal elements, oxides of rare earth metal elements or hydroxides of rare earth metal elements.
3. The pure inorganic stimuli-responsive sol according to claim 2, characterized in that: The concentration of the inorganic one-dimensional nanomaterial is 1-100 mg / mL.
4. The pure inorganic stimuli-responsive sol according to claim 1, characterized in that: The solution includes anions I, and the anions I include at least one of chloride ions, nitrate ions, borate ions, citrate ions, and acetate ions.
5. The pure inorganic stimuli-responsive sol according to claim 4, characterized in that: The concentration of anion I in the solution is 0.001-10M.
6. The pure inorganic stimuli-responsive sol according to claim 4, characterized in that: The solution also includes hydroxide ions, and the concentration of the hydroxide ions is below 1 mM.
7. A method for preparing a pure inorganic stimulus-responsive sol, characterized in that: The following steps are involved: Step (1), adding an inducer to the metal salt solution under stirring to form a uniform liquid; Step (2), adding liquid into a reaction kettle for reaction; Step (3), controlling the environmental hydroxide concentration to obtain a sol product.
8. The method for preparing a pure inorganic stimuli-responsive sol according to claim 7, characterized in that: The metal salt in step (1) includes a salt of a rare earth metal element.
9. The method for preparing a pure inorganic stimuli-responsive sol according to claim 8, characterized in that: The rare earth metal element is at least one of lanthanum, cerium, spectrium, promethium, samarium, europium and gadolinium.
10. The method for preparing a pure inorganic stimuli-responsive sol according to claim 7, characterized in that: The anion in the metal salt in step (1) includes at least one of nitrate ion, acetate, sulfate, hydrochloride, bromide, and iodide.
11. The method for preparing a pure inorganic stimuli-responsive sol according to claim 7, characterized in that: The concentration of the metal salt in step (1) is 0.1-10M.
12. The method for preparing a pure inorganic stimuli-responsive sol according to claim 7, characterized in that: In step (1), the inducing agent includes an alkaline solution.
13. The method for preparing a pure inorganic stimuli-responsive sol according to claim 12, characterized in that: The alkaline solution includes at least one of aqueous ammonia, sodium hydroxide and potassium hydroxide.
14. The method for preparing a pure inorganic stimuli-responsive sol according to claim 12, characterized in that: The inducing agent in step (1) also includes an oxygen-containing acid.
15. The method for preparing a pure inorganic stimuli-responsive sol according to claim 14, characterized in that: The oxygen-containing acid includes at least one of concentrated phosphoric acid or boric acid.
16. The method for preparing a pure inorganic stimuli-responsive sol according to claim 7, characterized in that: The reaction time of step (2) is less than 24 hours, and the reaction temperature is 60-300°C.
17. The method for preparing a pure inorganic stimuli-responsive sol according to claim 7, characterized in that: In step (3), the hydroxide concentration is controlled to be less than 1 mM.
18. The method for preparing a pure inorganic stimuli-responsive sol according to claim 7, characterized in that: The method for controlling the hydroxide concentration in step (3) is to use an acid.
19. The method for preparing a pure inorganic stimuli-responsive sol according to claim 18, characterized in that: The acid includes at least one of hydrochloric acid, nitric acid, boric acid, citric acid or acetic acid.
20. A method for converting a pure inorganic stimuli-responsive sol into a gel according to any one of claims 1 to 6, characterized in that: The stimulus response conditions include adding anions II that can have chelation and / or electrostatic effects with metal elements in inorganic one-dimensional nanomaterials into the pure inorganic stimulus response sol or changing the temperature of the pure inorganic stimulus response sol.
21. The method according to claim 20, characterized in that: The anion II that can have a chelating effect and / or electrostatic effect with the metal element in the inorganic one-dimensional nanomaterial includes at least one of hydroxide ion, phosphate ion, carbonate ion, molybdate ion, tungstate ion, titanate ion, sulfate ion, and bismuth ion.
22. The method according to claim 20, characterized in that: The anion II is a hydroxide ion.
23. The method according to claim 20, characterized in that: Changing the temperature of the pure inorganic stimuli-responsive sol is to increase the temperature of the sol.
24. A pure inorganic stimuli-responsive gel prepared by the method according to any one of claims 20 to 23.
25. A method for converting the pure inorganic stimuli-responsive gel according to claim 24 into a pure inorganic stimuli-responsive sol, characterized in that: The stimulus response conditions include removing the anion II or changing the gel temperature.
26. The method according to claim 25, characterized in that: The method for removing the anion II includes adding an acidic solution, dialysis or ultrafiltration.
27. The method according to claim 26, characterized in that: The acidic solution includes at least one of hydrochloric acid, nitric acid, boric acid, citric acid and acetic acid.
28. The method according to claim 26, characterized in that: The dialysis time is greater than 12 hours, and the ultrafiltration time is greater than 10 minutes; the external solution used in the dialysis includes at least one of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.
29. The method according to claim 25, characterized in that: Changing the gel temperature is to lower the gel temperature.
30. Application of a pure inorganic stimuli-responsive sol in sterilization, hemostasis, wound recovery, drug carrier, medical excipient, cosmetic material or sunscreen product, characterized in that: The method comprises at least a step of converting a sol into a gel and / or a step of converting a gel into a sol; The pure inorganic stimuli-responsive sol comprises an inorganic one-dimensional nanomaterial and a solution for dispersing the inorganic one-dimensional nanomaterial; The inorganic one-dimensional nanomaterials at least contain rare earth metal elements, and the positive charge of the rare earth metal elements causes the inorganic one-dimensional nanomaterials to repel each other to form a sol.
31. Application of a pure inorganic stimuli-responsive gel in sterilization, hemostasis, wound recovery, drug carrier, medical excipient, cosmetic material or sunscreen product, characterized in that: The method comprises at least a step of converting a gel into a sol and / or a step of converting a sol into a gel; the sol comprises an inorganic one-dimensional nanomaterial and a solution for dispersing the inorganic one-dimensional nanomaterial; The inorganic one-dimensional nanomaterials at least contain rare earth metal elements, and the positive charge of the rare earth metal elements causes the inorganic one-dimensional nanomaterials to repel each other to form a sol.
Citation Information
Patent Citations
Preparation method for high-activity lanthanum phosphate nanorod and application of high-activity lanthanum phosphate nanorod as photocatalyst
CN104609383A
Deformable stimuli responsive material and preparation method thereof and stimuli responsive flexible microelectrode array
CN107033279A
Cellulose nanocrystal-rare earth complex-polyvinyl alcohol composite hydrogel fluorescent probe, and preparation method and applications thereof
CN109897317A
Cerium dioxide nanorod hybrid multifunctional hydrogel, preparation method and application
CN114716817A
Biomolecular organogel, xerogel and methods for preparing the same
KR1020090043882A
Cited By
Dressing for repairing skin defect wound as well as preparation method and application of dressing
CN121197479A